An integrative view on vacuolar pH homeostasis in Arabidopsis thaliana: Combining mathematical modeling and experimentation. (2nd May 2021) - Holzheu, Pascal; Krebs, Melanie; Larasati, Catharina; Schumacher, Karin; Kummer, Ursula
SUMMARY: The acidification of plant vacuoles is of great importance for various physiological processes, as a multitude of secondary active transporters utilize the proton gradient established across the vacuolar membrane. Vacuolar‐type H + ‐translocating ATPases and a pyrophosphatase are thought to enable vacuoles to accumulate protons against their electrochemical potential. However, recent studies pointed to the ATPase located at the trans‐Golgi network/early endosome (TGN/EE) to contribute to vacuolar acidification in a manner not understood as of now. Here, we combined experimental data and computational modeling to test different hypotheses for vacuolar acidification mechanisms. For this, we analyzed different models with respect to their ability to describe existing experimental data. To better differentiate between alternative acidification mechanisms, new experimental data have been generated. By fitting the models to the experimental data, we were able to prioritize the hypothesis in which vesicular trafficking of Ca 2+ /H + ‐antiporters from the TGN/EE to the vacuolar membrane and the activity of ATP‐dependent Ca 2+ ‐pumps at the tonoplast might explain the residual acidification observed in Arabidopsis mutants defective in vacuolar proton pump activity. The presented modeling approach provides an integrative perspective on vacuolar pH regulation in Arabidopsis and holds potential to guide further experimental work. Significance Statement: The study represents the first integrative computational model of pH homeostasis in the vacuole of Arabidopsis thaliana . With its aid and based on experimental data, we were able to study the feasibility of different hypotheses for experimental observations of pH changes after perturbation.